The Impact of Female Labor Force Participation on Regional Economic and Income Convergence - Panjaitan, Dian Verawati; Nuryartono, Nunung; Pasaribu, Syamsul Hidayat; Lay, Jann (ETIKONOMI, 2025)
Research originality: Women tend to be chosen as the non-labor force, even though they are potential workers who can contribute directly to the economy. Their level of education influences this contribution.   Research objectives: This research examined the impact of female labor force participation on regional economic and income convergence. Research methods: Pooled Least Squares (PLS) and panel data estimation were conducted using cross-sectional data on 472 cities/districts across Indonesia between 2016 and 2022. Empirical result: The findings reveal that female labor force participation significantly enhances regional economic growth only when women have at least a senior high school education. However, their contribution to accelerating economic convergence remains suboptimal, as most female workers are elementary school graduates. Implications: To improve the contribution of the female workforce to the economy, the government should extend compulsory education from 9 to 12 years, expand access to non-formal education for women, and establish a female-friendly labor market through job flexibility and improved childcare access. JEL Classification: I25, J21, E12, J20